The use of a mathematical model of the chromatographic column for processing chromatograms with overlapping peaks. - A. V. Anisimov; P. G. Rumyantsev; V. I. Zhuchkov (Тонкие химические технологии, 2007)
A method is suggested to process overlapping chromatographic peaks with the use of a mathematical model of the chromatographic column. The method enables determining the composition of the mixture to be analyzed even in case of completely overlapping peaks.